2019
DOI: 10.1111/jcmm.14435
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA LINC00526 represses glioma progression via forming a double negative feedback loop with AXL

Abstract: Glioma is the most common primary intracranial carcinoma with extremely poor prognosis. The significances of long non‐coding RNA (lncRNA) involved in glioma have been started revealed. However, the expression, roles and molecular mechanisms of most lncRNAs in glioma are still unknown. In this study, we identified a novel lncRNA LINC00526, which is significantly low expressed in glioma. Low expression of LINC00526 is correlated with aggravation and poor survival in glioma. Functional assays revealed that ectopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 58 publications
(131 reference statements)
2
11
0
Order By: Relevance
“…These results are similar to the reported role of RA in colorectal cancer [33]. Numerous studies have shown that the PI3K/Akt/NF-κB pathway is closely related to HCC progression [34][35][36]. In line with these reports, our results showed that the PI3K/Akt/NF-κB signal pathway is involved in the anti-tumor effects of RA in HCC.…”
Section: Discussionsupporting
confidence: 92%
“…These results are similar to the reported role of RA in colorectal cancer [33]. Numerous studies have shown that the PI3K/Akt/NF-κB pathway is closely related to HCC progression [34][35][36]. In line with these reports, our results showed that the PI3K/Akt/NF-κB signal pathway is involved in the anti-tumor effects of RA in HCC.…”
Section: Discussionsupporting
confidence: 92%
“…Abnormal expression of Gas6/AXL has been confirmed in more and more human malignancies, including pancreatic cancer, breast cancer, NSCLC, glioma, and so on. 4,18 AXL promotes tumor cell self-renewal, EMT, and drug resistance, and it has become a novel attractive molecular target for anti-neoplastic drug discovery. 5,6,19,20 Studies demonstrated that AXL promoted osteosarcoma progression through activating AKT expression and that it was downregulated by F I G U R E 6 The expression of linc00852, AXL mRNA and miR-7-5p in osteosarcoma tissues and the relationship among them.…”
Section: Discussionmentioning
confidence: 99%
“…Our result is consistent with the results of previous studies. LINC00526 is a long intergenic non-protein-coding RNA, and one study has demonstrated that it suppresses glioma progression [37]. ARL14 (ADP Ribosylation Factor Like GTPase 14) is a protein-coding gene that participates in GTP binding and signal transduction [38].…”
Section: Discussionmentioning
confidence: 99%